2007
DOI: 10.1097/01.htr.0000271115.29954.27
|View full text |Cite
|
Sign up to set email alerts
|

Objective Documentation of Traumatic Brain Injury Subsequent to Mild Head Trauma

Abstract: Functional brain imaging data collected in a resting state can provide objective evidence of brain injury in mild blunt head trauma patients with persistent postconcussive somatic and/or cognitive symptoms. MEG proved to be particularly informative for patients with cognitive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
143
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(156 citation statements)
references
References 43 publications
(56 reference statements)
9
143
0
1
Order By: Relevance
“…Human studies by Lewine et al, and our laboratory showed that the brains of mTBI patients generate abnormal low-frequency magnetic fields that can be measured and localized by resting-state MEG (Huang et al, 2009(Huang et al, , 2012Lewine et al, 1999Lewine et al, , 2007. MEG was also found to be more sensitive than conventional MRI or EEG in detecting abnormalities in mTBI patients (Lewine et al, 1999(Lewine et al, , 2007.…”
Section: Clinicalmentioning
confidence: 72%
See 1 more Smart Citation
“…Human studies by Lewine et al, and our laboratory showed that the brains of mTBI patients generate abnormal low-frequency magnetic fields that can be measured and localized by resting-state MEG (Huang et al, 2009(Huang et al, , 2012Lewine et al, 1999Lewine et al, , 2007. MEG was also found to be more sensitive than conventional MRI or EEG in detecting abnormalities in mTBI patients (Lewine et al, 1999(Lewine et al, , 2007.…”
Section: Clinicalmentioning
confidence: 72%
“…These experiments concluded that cortical de-afferentation was an important factor in abnormal delta-wave production, owing to WM lesions (i.e., axonal injury) and/or defects in the cholinergic pathway (Schaul, 1998). In the human brain, the projections of cholinergic pathways highly overlap with the WM fiber tracts (Selden et al, 1998), which make the cholinergic pathways similarly susceptible as the WM tracts to TBI.Human studies by Lewine et al, and our laboratory showed that the brains of mTBI patients generate abnormal low-frequency magnetic fields that can be measured and localized by resting-state MEG (Huang et al, 2009(Huang et al, , 2012Lewine et al, 1999Lewine et al, , 2007. MEG was also found to be more sensitive than conventional MRI or EEG in detecting abnormalities in mTBI patients (Lewine et al, 1999(Lewine et al, , 2007.…”
mentioning
confidence: 91%
“…If boxing is considered a model for detecting "pre-clinical" or asymptomatic brain injury, recent diffusion tensor imaging studies have demonstrated abnormalities in boxers (Chappell et al, 2006;Zhang et al, 2006b). Thus, animal and human studies support the contention of injury on a continuum, implicating that understanding the variables that relate to severity of injury are likely very important in understanding neuropsychological sequelae (see Wilde et al, in press;Lewine et al, 2007).…”
Section: Is Brain Injury On a Continuum: Concussion R Severe Tbi?mentioning
confidence: 93%
“…Furthermore, MEG measures of functional connectivity are comparable to fMRI, but include the additional dimensions of time and oscillatory frequency that are present in neurophysiological data 23. Using a resting state protocol, it has been shown that the location of slow waves in the delta (1–4 Hz) frequency range corresponded to sites of brain injury24, 25 and differentiated individuals with mTBI from controls 26. Functional connectivity metrics acquired from resting state MEG recordings demonstrated decreases in functional connectivity even in mTBI27 and correlated with cognitive recovery and neuropsychological assessments in acquired brain injury 28.…”
Section: Introductionmentioning
confidence: 99%